THE INFLUENCE OF CUSTOMER PURCHASE DECISION ON CUSTOMER SATISFACTION AND ITâ€™S IMPACT TO CUSTOMER LOYALTY - Susanto, Andhika H. (Universitas Sam Ratulangi, 2013)
With population above 434 thousand and high ranks per capita Manado city becomes a very huge potential for food industry, including fast food. The available of quick serve food become requirement of society in line with fast mobility. The result is lot of new fast food brands enter to the market. From my observation some kind of fast food restaurant in Manado is KFC, Texas Chicken, Pizza Hut, Mc Donald, and so on. The purpose of this research is to investigate the influence of customer purchase decision toward customer satisfaction and the impact to customer loyalty toward KFC brands. The customer purchase decision is measured through some factor such as cultural factor, social factor, and personal factor. Meanwhile customer satisfaction is measured through some indicator such as promotionÂ¸ service quality, and brand. The customer loyalty is measure through satisfaction, linking of the brand, and commitment. The research objectives are: (1) to identify and analyze customer purchase decisions effect on customer satisfaction, (2) to identify and analyze customer satisfaction effect on customer loyalty, and (3) to identify and analyze customer purchase decisions effect on customer loyalty. The population in is students, workers, and fast food customer with sample as many as 130 respondents using Structural Equation Modelling (SEM). The result is customer purchase decission has significant influence to customer satisfaction, customer satisfaction has significant influence to customer loyalty, and also customer purchase decission has significant influence to customer loyalty. Keywords: customer purchase decision, customer satisfaction, customer loyalty